2013
DOI: 10.1007/s13277-013-0813-0
|View full text |Cite
|
Sign up to set email alerts
|

DLC1 as a regulator of proliferation, invasion, cell cycle, and apoptosis in cutaneous squamous cell carcinoma

Abstract: Increasing evidence has demonstrated that the tumor suppressor gene deleted in liver cancer-1 (DLC1) is tightly implicated in the development and progression of tumors and is verified to be downregulated in a variety of tumors. However, the roles and precise molecular mechanisms of DLC1 in cutaneous squamous cell carcinoma (cutaneous SCC) remain to be elucidated. In the present study, we confirmed the reduced level in cutaneous SCC tissues and cells, and DLC1 mRNA relative level in cutaneous SCC tissues with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…We found that SCCderived A431 cells, previously tested for their invasiveness and metastatic capacity in vivo [46,49], show high levels of activated IKK in the nucleus mainly corresponding to the previously identified p45-IKKa isoform (Fig. 3a), compared with the low amounts of activated full-length IKKa or b (85/87 kDa, respectively).…”
Section: Targeting Ikk Promotes Apoptosis and Reduces Cscc Cell Migrasupporting
confidence: 51%
“…We found that SCCderived A431 cells, previously tested for their invasiveness and metastatic capacity in vivo [46,49], show high levels of activated IKK in the nucleus mainly corresponding to the previously identified p45-IKKa isoform (Fig. 3a), compared with the low amounts of activated full-length IKKa or b (85/87 kDa, respectively).…”
Section: Targeting Ikk Promotes Apoptosis and Reduces Cscc Cell Migrasupporting
confidence: 51%
“…68,69 It will thus be interesting to see if breast cancers with 8p-loss might respond better to neoadjuvant chemotherapy as compared to those lacking this alteration. The fact that 8p deletions were markedly associated with rapid cell proliferation is potentially caused by deletion-dependent down-regulation of several wellknown cell-cycle control genes located at 8p21, 8p22 and 8p23, including for example LZTS1, an inhibitor of the Cdk1/cyclin B1 complex, 23 PINX1, which prolongs G0/S1 phase, 70 DLC1, an inducer of apoptosis, 71 and MTUS1, which delays progression of mitosis by prolonging metaphase. 21 Further steps for identification of putative tumor suppressor genes would include comparison between expression and copy numbers of 8p genes followed by functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Cyclin D1 seems to be downregulated in specific skin cancers, especially in squamous cell carcinoma (SCC) by an altered TSG such as the gene Deleted in Liver Cancer 1 (DLC1). [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…TSGs can induce skin cancers as a result of a loss of their normal function, i.e., these proteins suppress the development of cancer. [ 1 2 3 4 5 ] A recent review documented 716 human TSG (637 coding and 79 noncoding genes), 628 mouse TSG, and 567 rat TSG. [ 1 2 3 4 5 6 7 ] Since a single normal allele will express the wild-type TSG, the majority of human TSGs are recessive; specifically, both alleles must be defective for the cell to be susceptible to tumor development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation